(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the characteristics, evolution and outcome of patients co-infected with COVID-19 and tuberculosis (TB). Methodology: In order to answer the guiding question “What are the risks of coinfection by COVID-19 and tuberculosis?”, an integrative literature review, qualitative, with a descriptive approach, was carried out in the Google Scholar, PubMed, Cochrane Library, SciELO and LILACS databases, using the descriptors “COVID -19”, “Tuberculosis” and “Co-infection”. Inclusion criteria were: article available in full, published in 2020, in Portuguese, English and/or Spanish. Articles unrelated to the topic, with a focus on statistical tools, isolated abstracts, book chapters, editorials, review articles, technical sheets, theses, dissertations and course completion papers were excluded. Results: 8 articles were included. Most of the co-infected patients were male, with a mean age of 47.19 years. The most reported symptoms were fever, cough, dyspnoea and headache. The main laboratory changes included elevation of C-reactive protein, erythrocyte sedimentation rate, D-dimer and fibrinogen. Imagological findings such as opacifications, pleural effusion, “sprouting tree”, ground glass, cavitations, atelectasis and thickening of the lobar septum were frequent. Co-infection was more linked to severe cases of the disease and lethality was up to 33.3%. Socially, co-infection results in difficulties in differential diagnosis, morbidity in vulnerable groups and difficulty in accessing treatment in a pandemic scenario. Conclusion: Some studies differed on lethality, but it was possible to observe a trend towards an association between the severity of the clinical course in co-infected patients.